3D printed smart glove with pyramidal MXene/Ecoflex composite-based toroidal triboelectric nanogenerators for wearable human-machine interaction applications. (February 2023) - Zhang, Shipeng; Rana, SM Sohel; Bhatta, Trilochan; Pradhan, Gagan Bahadur; Sharma, Sudeep; Song, Hyesu; Jeong, Seonghoon; Park, Jae Yeong
Abstract: Self-powered sensors based on triboelectric nanogenerators (TENGs) have shown great advantages in human-machine interactions. However, the complex preparation process and high cost of conventional electrodes hinder their practical implementation. In this study, we develop a wearable self-powered toroidal triboelectric sensor (STTS) with a pyramidal structure for self-powered human-machine interactions based on an extremely simplified design strategy. 3D printing technology is employed to fabricate pyramidal arrays on MXene/Ecoflex nanocomposites, thus providing a comfortable space between the finger skin and the negatively charged layer to overcome the space requirements in traditional triboelectric-based sensors. Furthermore, the developed pyramidal structure of the nanocomposite and flexible conductive fabric electrodes assembled with 3D-printed gloves based on the flexible TPU material maintained the wearability of the sensing system. The flexible and simplified single-electrode design strategy of the STTS can be easily worn on the human hand for comfortable and natural interaction with machines and devices. The high peak-to-peak voltage (19.91 V), high sensitivity (0.088 VkPa −1 ), and wide pressure detection range (0–120 kPa) enable the generation of high-quality output signals for the accurate detection of various finger movements exhibiting great potential for use in human-machine interaction applications in next-generation artificial intelligence and interactive devices. Graphical Abstract: ga1 Highlights: MXene/Ecoflex nanocomposites and pyramidal structured TENG for increasing performance. A High-performance 3D-printed glove based on a simplified structure for self-powered human-machine interaction. The high peak-to-peak voltage, high sensitivity, and wide pressure detection range generate high-quality output signals. The use of conductive fabrics as electrodes provides good wear resistance, flexibility, and mechanical stability. The pyramidal structure allows the sensor to operate in contact separation mode without any spacing structure.